Loan Supply and Demand in Rural Regional Bank: Evidence from Indonesia - Rofikoh Rokhim; Nadia Listiyani (International Journal of Small and Medium Enterprises and Business Sustainability, 2017)
This study tries to identify the impact of third party funds, average lending rate (ALR) of working capital, non-performing loans (NPLs), and gross domestic regional products (GDRP) on loan supply in Rural Regional Banks (RRBs). In addition, this research also analyzes GDRP, region’s inflation, and ALR of working capital that influence loan demand of RRBs. This study uses panel data and regression method with random effect model from regional and time differences. The study proves that third party funds, ALR of working capital, NPL, and GDRP simultaneously have significant affects on the loan supply. Then GDRP, region’s inflation, and ALR of working capital simultaneously affect the loan demand.